Oral Health within Tobacco Control Policies: Global and Brazilian Perspectives - , Luiz Carlos Trevia Morais Correia Viana, José Evando da Silva-Filho, Larissa Pinheiro Barreto, Fábio de Almeida-Gomes, Christina César Praça-Brasil (Archives of Current Research International, 2025)
Aims: This integrative review aimed to examine how public anti-smoking policies address oral health and the role of dentists in tobacco control, highlighting gaps in policy integration and professional involvement. Methodology: The literature search was performed using the electronic databases PubMed and Google Scholar, covering publications from January 1995 to August 2024. The search terms “anti-smoking policies” AND “oral health” were applied using Boolean operators. Seventeen relevant studies were identified. The analysis focused on four main themes: (1) dentists’ role in smoking cessation; (2) evaluation of tobacco prevention programs; (3) tobacco-related content in dental education; and (4) public awareness of tobacco’s oral health effects. Results: Dentists are in a strategic position to support smoking cessation through brief interventions in clinical practice. However, barriers such as insufficient training, lack of institutional support, time constraints, and tobacco use among dental students limit their engagement. Gaps in dental curricula and the low visibility of oral health risks in public campaigns were also noted. Some initiatives, such as Brazil’s Tobacco Control Program and the WHO’s MPOWER strategy, show potential for better integrating oral health into broader tobacco control policies. Conclusion: Dentists have substantial potential to contribute to tobacco cessation and control strategies, yet their role remains underrepresented in public health policies. Strengthening dental education, professional training, and explicit inclusion of oral health in anti-smoking policies is essential to enhance the effectiveness of tobacco control initiatives and ensure comprehensive public health outcomes.